Comparison analysis between Aquarius sea surface salinity and World Ocean Database in situ analyzed sea surface salinity. Issue 11 (28th November 2014) - Reagan, James; Boyer, Tim; Antonov, John; Zweng, Melissa
Abstract A new monthly sea surface salinity (SSS) product calculated from profile data within the World Ocean Database (WOD) is compared and contrasted with Aquarius SSS, both standard and Combined Active‐Passive (CAP) products, from September 2011 through September 2013. Aquarius exhibits similar biases as shown in previous comparison SSS studies, with negative biases in the tropics transitioning to positive biases in the higher latitudes when compared to WOD SSS. These biases are generally much weaker in CAP than the standard version, indicating that the biases are strongly related to the differences in algorithms used to retrieve satellite SSS. Non‐Argo data utilized in the study are shown to be of great use to validate Aquarius in regions with little to no Argo coverage and helps provide SSS measurements in regions where there are known errors in Aquarius retrievals. The annual cycle of WOD and Aquarius is found to be very similar, with Aquarius being generally more coherent and robust. All three products' annual cycles compared favorably to the World Ocean Atlas 2013. The interannual changes in all three products generally corresponded well to one another and to changes in evaporation and precipitation (E‐P). Overall, Aquarius compares very well with in situ sea surface salinity fields under multiple comparison examinations; however, both products have their own strengths and weaknesses and a synthesis of the two should be used to study global scale SSS variability.